2002
DOI: 10.1177/095632020201300502
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Replication by an HIV-1 Dependent Ribozyme Expression Vector with the Cre/loxP (ON/OFF) System

Abstract: Antiviral strategies to inhibit HIV-1 replication have included the generation of gene products that provide the intracellular inhibition of an essential viral protein or RNA. When used in conjunction with the HIV-1 long terminal repeat (LTR), an inducible promoter dependent on the virus-encoded trans-activator (tat), relatively high background activity is still observed in the absence of tat (Caruso & Klatzmann, 1992; Dinges et al., 1995). In order to circumvent this problem, we used the Cre/loxP (ON/OFF) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However, the pLTR-Cre showed slight expression of the luciferase gene in HIV-1 uninfected HeLa CD4 + cells. [18] Recently, Miyake et al reported the use of the LTR promoter including the region from the 5 U3 to the middle of gag. [20] Hence, we also constructed an HIV-1-specific Cre expression vector that includes the LTR-gag-p17 promoter (from the 5 LTR U3 to the end of gag-p17, 1.2 kb, Figure 1).…”
Section: Design and Construction Of An Hiv-1-dependent Cre Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the pLTR-Cre showed slight expression of the luciferase gene in HIV-1 uninfected HeLa CD4 + cells. [18] Recently, Miyake et al reported the use of the LTR promoter including the region from the 5 U3 to the middle of gag. [20] Hence, we also constructed an HIV-1-specific Cre expression vector that includes the LTR-gag-p17 promoter (from the 5 LTR U3 to the end of gag-p17, 1.2 kb, Figure 1).…”
Section: Design and Construction Of An Hiv-1-dependent Cre Expressionmentioning
confidence: 99%
“…After digestions of the PCR amplified LTR product with SpeI and EcoRI, and the pGEM-Cre vector with MfeI and BamHI, each fragment was ligated into the SpeI/BamHI sites of the plasmid containing the Cre gene (pBS185), to yield pLTR-gag-p17-Cre. In order to add the XhoI cloning site to the plox-Rz-U5 [18] fragment, plox-Rz-U5 was first digested by NotI and SpeI. This fragment was then cloned into the NotI and SpeI sites in pVAX-1 (Invitrogen) to yield pVAX-LRU, which contained the needed XhoI site.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RT-PCR reactions were used to establish the level of uncleaved HIV-1 mRNA (product I and II). [28] The uncleaved HIV-1 mRNA was amplified by the vifF1and tat-F1 primers, and the vif-R and tat-R primers ( Figure 5A). The level of product I and II were expected to decrease after cleavage of the HIV-1 mRNA.…”
Section: Effect Of a Combination Of Rnase P And Trnase Zl-associated mentioning
confidence: 99%